Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Section 11.1 - Solving Quadratic Equations by Completing the Square - Exercise Set: 86

Answer

$\sqrt 13$

Work Step by Step

$a = 1, b=-3, c=-1$ $\sqrt {b^2-4ac}$ =$ \sqrt {(-3)^2 - (4\times1\times-1)}$ =$\sqrt {9-(-4)}$ =$\sqrt {9+4}$ =$\sqrt 13$ =$\sqrt 13$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.